4 - Regards croisés sur l’économie pastorale de la Tarka au Niger - Maman, Abdo Hassan (Africa Development, 2021)
This paper analyzes the pastoral economy of Tarka. The present crisis showed the limits of cattle breeder strategies’ facing environmental shocks. The poor pastoral households are victims of decentralized governance. In unfavourable economic situation, the cereal products and animals exchange fixed by monopolies decreases their buying power, and increases their vulnerability and their capacities deprivation. The industrialization of animals breeding through half intensive of stock breeding becomes useful to increase their resilience.